Antibiotic preferences for childhood pneumonia vary by physician type and European region. Issue 2 (29th April 2016) - Bielicki, Julia A.; Barker, Charlotte I.S.; van der Velden, Alike W.; Sharland, Mike; van Esso, Diego; Hadjipanayis, Adamos; del Torso, Stefano; Grossman, Zachi
Antibiotics are the most commonly prescribed medicines for acutely unwell children worldwide [1]. Many of these antibiotic prescriptions are issued in a primary care setting [2–4]. Despite this, a robust evidence base for agent selection in primary care is lacking for many childhood indications, including community-acquired pneumonia (CAP). In an era of increasing antibiotic resistance, with optimal antibiotic use being paramount to preserve this precious resource, trials involving ambulatory patients representative of those seen in primary care are needed to address this gap. Survey of EAPRASnet and @PREPARE_EUROPE members reveals heterogeneity of antibiotic choice for childhood pneumonia http://ow.ly/4mIS2P